Significant contribution from impurity-band transport to the room temperature conductivity of silicon-doped AlGaN. (24th January 2018) - Pampili, Pietro; Dinh, Duc V; Zubialevich, Vitaly Z; Parbrook, Peter J
Abstract: Silicon-doped n -type (0 0 0 1) AlGaN materials with 60% and 85% AlN content were studied close to the doping condition that gives the lowest resistivity (Si/III ratios in the ranges 2.8–34  ×  10 −5 and 1.3–6.6  ×  10 −5, respectively). Temperature-dependent conductivity and Hall-effect measurements showed that, apart from the diffusion-like transport in the conduction band, a significant amount of the conductivity was due to phonon-assisted hopping among localized states in the impurity band, which became almost completely degenerate in the most doped sample of the Al0.6 Ga0.4 N series. In the doping range explored, impurity-band transport was not only dominant at low temperature, but also significant at room-temperature, with contributions to the total conductivity up to 46% for the most conductive sample. We show that, as a consequence of this fact, the measurements of Hall carrier concentration and Hall mobility using the usual single-channel approach are not reliable, even at high temperatures. We propose a simple method to separate the contributions of the two channels. Our model, although only approximate, can be used to gain insight into the doping mechanism: particularly it shows that the room-temperature free-electron concentration in the conduction band of the Al0.6 Ga0.4 N material reaches its maximum at about 1.6  ×  10 18 cm −3, well below the value that would have been obtained with the standard single-channel analysis of the data. This maximum is already achieved at dopant concentrations lower than the one that gives the best conductivity. However, further increase of the doping levels are required to enhance the impurity-band channel, with concentrations of the carriers participating in this type of transport that increase from 2.1  ×  10 18 cm −3 up to 4.3  ×  10 18 cm −3 . For the Al0.85 Ga0.15 N, even though it was not possible to estimate the actual carrier concentrations, our measurements suggest that a significant impurity-band channel is present also in this material.